LABOR POTENTIAL OF RURAL TERRITORIES: SOCIO-ECONOMIC ASPECT OF PEASANT (FARM) FARMS IN THE REGION - Yuri Viktorovich Bukhvostov (Science and Innovation Center Publishing House, 2020)
In a difficult economic situation, the Russian agricultural sector has the opportunity to improve the efficiency of agricultural production. In the situation of uneven socio-economic development of rural territories, the establishment of a policy on import substitution of agricultural products, as well as the implementation of the Strategy for long-term socio-economic development of the Russian agro-industrial complex and the Concept of sustainable development of rural territories, the problem of forming the labor potential of rural territories is of particular relevance.